Пошаговое объяснение:
1.
а)
-2,3 + 1,7 = -0,6
б)
-5/7 - 2/3 = -15/21 - 14/21 = -29/21 = - 1 8/21,
в)
1 2/5 - 7 = 7/5 - 35/5 = - 28/5 = - 5 3/5,
2.
-2 - (-7) + (-6) - 9,5 = -2 + 7 - 6 - 9,5 = -10,5
3.
а)
-2,3 * 0,3 = -0,69,
б)
(-0,3) * (-5/6) = 3/10 * 5/6 = 1/4 (или 0,25),
в)
(-2)⁵ = -32,
4.
1 1/3 * (-3/4) - (- 2 1/7) * 1 2/5 = 2,
1) 1 1/3 * (-3/4) = - 4/3 * 3/4 = -1,
2) -2 1/7 * 1 2/5 = -15/7 * 7/5 = -15/5 = -3,
3) -1 - (-3) = -1 + 3 = 2,
5.
-(-2) + 3 + х = -4,
2 + 3 + х = -4,
х = -4 - 2 - 3,
х = -9